Decolonisation of the nursing education curriculum in Gauteng province, South Africa: A concept analysis - Agnes Makhene (AOSIS, 2023)
Background: Decolonisation of the nursing education curriculum has become more important than ever. The nursing profession has been colonised since its founding era by Florence Nightingale. Victorian curriculum has been taught over decades in nursing. There is a knowledge gap of what decolonisation means in the profession. Aim: The purpose of this article is to describe the concept analysis process that was followed to clarify the concept of 'decolonisation' of the curriculum, provide conceptual meaning in nursing education, and formulate a theoretical definition. Setting: Nursing education practice in Gauteng. Methods: Definitions, nature, characteristics, and uses of decolonisation were sought and the researchers explored 52 publications, which included dictionaries, encyclopaedias, thesauri, conference articles, research reports, journal articles and subject-related literature across multiple disciplines, to critically analyse the concept 'decolonisation'. A 10-year period from 2012 to 2022 was used to search several databases. Results: Defining attributes that included antecedents, process and consequences of decolonisation emerged. The antecedents were awareness, identification of colonial knowledge and thought, colonial attitudes, colonialism, racism, exclusion, denial of colonial systems and curriculum and colonial legacies in nursing education. Events after decolonisation are called consequences. Conclusion: The formulated theoretical definition of 'decolonisation' will be operationalised as further research takes place to come up with a conceptual framework for a decolonised socially just nursing curriculum. Contribution: This study aimed to contribute towards the understanding of what decolonisation means within nursing education and lead to development of models, theories, and strategies on how decolonisation of the nursing curriculum can be undertaken.